Correlation Between Testis Weight, Testis Volume, and Total Sperm Count in the Indonesian Domestic Cats (Felis catus) - Mardatillah, Karisma; Rahman, Aulia Miftakhur; Prasetyaningtyas, Wahono Esthi; Boediono, Arief (Jurnal Veteriner, 2023)
Information regarding the domestic cat as a model animal in the biomedical research has not been widely carried out. This study was aimed to see the correlation between testicular weight, testicular volume and total sperm count between the left testicle, right testicle and both testes. In addition, this study was aimed to examine the effect of testicular weight and volume on quantitative histomorphometry of the testes in domestic cats in Indonesia. The results showed that there was no difference between the left and right testes. Testes weight has a positive and highly significant correlation with testes volume and total sperm count, both in the left, right, and both testes. The heavier the weight of the testes, the wider the diameter of the seminiferous tubules, the wider the lumen, and the taller the tubular epithelium. It can be concluded that the increase in testicular weight is in line with the increase in cells in the seminiferous tubules.